Epidemiological profile of tuberculosis in the elderly in Belém-PA between 2017-2021 (Research, Society and Development, 2023)
Objective: Time series analysis of tuberculosis cases in the elderly and evaluation of the epidemiological profile. Method: This is a descriptive, cross-sectional and quantitative study on the cases of tuberculosis in the elderly based on information from DATASUS and SINAN, between 2017 and 2021 in Belém, Pará. Results: The prevalence of tuberculosis in the period evaluated was highest in 2019 (23.05%) with a downward trend in later years. The most used diagnostic method was bacilloscopy (51.55%) and the most prevalent form of extrapulmonary tuberculosis was pleural (5.52%) and ganglionar (1.47%). Discussion: The Amazon region presents a high prevalence of tuberculosis, and despite the tendency to decrease the number of cases from 2020, indicators such as abandonment of treatment, reduction of notifications and decrease in the dispensation of drugs. The elderly population presents a higher risk of complications related to the disease as well as a later diagnosis, and the continued exposure to bacilliferous individuals at home during social isolation may contribute to the problem. Conclusion: the need for intensification of socio-educational actions to identify symptoms and perform complementary tests when there is diagnostic suspicion as a major strategy in the early detection of tuberculosis.